Microbial Pretreatment of Chicken Feather and Its Co-digestion With Rice Husk and Green Grocery Waste for Enhanced Biogas Production - Saba, Marium; Khan, Anum; Ali, Huma; Bibi, Amna; Gul, Zeeshan; Khan, Alam; Rehman, Muhammad Maqsood Ur; Badshah, Malik; Hasan, Fariha; Shah, Aamer Ali; Khan, Samiullah (Frontiers in Microbiology, 2022)
To utilize wastes and residues sustainably and excellently, there is need to fend for efficient methods and resources for biogas production. Therefore, production of biogas to utilize poultry waste represents one of most important routes towards reaching global renewable energy targets. In this respect, current study involves microbial pretreatment of chicken feather waste, followed by its co-digestion with green grocery waste and rice husk in batch and continuous reactors. Microbial pretreatment of chicken feathers by keratinase secreting Pseudomonas aeruginosa was an effective and eco-friendly approach to make its recalcitrant structure available as raw source for biogas production. Current study also addressed to establish balanced C/N ratio in the reactors. Results demonstrated that feathers microbial pretreatment, percent increase in biogas yield was 1.1% as compared to mono-digestion. While the co-digestion of chicken feathers hydrolysate with green-grocery waste in continuous fermentation has also enhanced biogas yield and high efficiency of overall process.